2014
DOI: 10.1007/s00405-014-3256-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of three-dimensional Doppler ultrasonography in assessing nodal metastasis of head and neck cancer

Abstract: The aim of this study was to assess the clinical usefulness of three-dimensional (3D) color Doppler ultrasonography with a novel predictive model in the detection of cervical metastasis of untreated head and neck squamous cell carcinoma patients. We assessed cervical lymph node metastasis in 52 head and neck squamous cell carcinoma patients by 3D color Doppler ultrasonography, magnetic resonance imaging, and [(18)F] fluorodeoxyglucose positron emission tomography with computed tomography. Pathologic analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Ahuja et al reported poor agreement in the assessment of vascular patterns. 26 Lai et al evaluated the accuracy of 3D ultrasound in nodal staging of head and neck cancer and reported 92.6% accuracy. 25 However, these studies did not compare the performance of 2D and 3D ultrasound in differentiating benign and malignant LNs, nor did they report sensitivity or specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahuja et al reported poor agreement in the assessment of vascular patterns. 26 Lai et al evaluated the accuracy of 3D ultrasound in nodal staging of head and neck cancer and reported 92.6% accuracy. 25 However, these studies did not compare the performance of 2D and 3D ultrasound in differentiating benign and malignant LNs, nor did they report sensitivity or specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al showed a sensitivity and specificity of 78.9% and 99%, higher than MRI or PET/CT. 26 Lai et al evaluated the accuracy of 3D ultrasound in nodal staging of head and neck cancer and reported 92.6% accuracy. 27 Zhou et al reported 3D ultrasound to be more accurate in the evaluation of LN vascularity, yielded a higher sensitivity than 2D ultrasound alone in differentiating benign and malignant LNs in head and neck cancer (95% vs 81%).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, attempts have been made to use ultrasonography in this area. Ultrasonography has been used to evaluate laryngeal tumors in a few studies since the 1970's and some of these have proved that ultrasonography can assist in tumor staging in patients with advanced laryngeal cancer (1,(6)(7)(8). With the application of a wide band and high frequency ultrasonic probe, ultrasound can clearly show the main structures of laryngeal cartilage, ligament, muscle, pre-epiglottic space and para-glottic space for their superficial location and, to a certain extent, the sound transmission of laryngeal cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The occupying solid tumor displaces the throat cavity and infiltrates and destroys the thyroid cartilage. It provides a favorable condition for ultrasound imaging (6,7). The high resolution ultrasound for laryngeal imaging has the advantage of real-time, dynamic, multi-plane, as well as multi-directional, imaging, which limits MRI and CT imaging (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation